The sum of three numbers is 2100. The first number (x) is equal to the sum of the other two (y and z) which are equal to each other. What are the three numbers (x, y, and z)? A) (1050, 525, 525) B) (1050, 524, 525) C) (1050, 526, 523) D) (1051, 525, 524)

Answers

Answer 1
Answer:

Answer:

Let's solve the problem step-by-step:

We are given that the sum of three numbers is 2100. Let's call the first number x and the other two numbers y and z.

From the information given, we know that x = y + z, and y = z (the other two numbers are equal to each other).

Substituting y = z into x = y + z, we have x = 2z.

We are also given that the sum of the three numbers is 2100. So, we can write the equation x + y + z = 2100.

Substituting x = 2z and y = z, we have 2z + z + z = 2100.

Simplifying the equation, we have 4z = 2100.

Dividing both sides of the equation by 4, we find z = 525.

Substituting z = 525 back into y = z, we find y = 525.

Finally, substituting z = 525 and y = 525 back into x = 2z, we find x = 1050.

Therefore, the three numbers are x = 1050, y = 525, and z = 525.

Among the options provided, the correct answer is A) (1050, 525, 525).


Related Questions

2x +3y=9 4x+6y=7 solve using Gauss-Jordan method to solve each system of equations
Which of the following sums would be under the radical symbol to find the distance between the points (7, -1) and (-8, -9)?
Calculate ten minus three point nine
Karl has stamps in his desk drawer. The possible combinations of stamps are shown below.
A stereo costs £320. In a sale it is reduced by 25%. What is the sale price?

What is the area of a rectangle with side of length 4/5 foot and 1/2 foot.

Answers

you multiply 4/5 and 1/2 and you get 4/10 which is simplified to 0.4 
which equals..
0.4 feet^2 in area

C. 59 x 5 - 25 x 5-30​

Answers

Answer: 140

Step-by-step explanation:

First we do all the multiplication parts due to BODMAS. This will now become:

==> 295 - 125 - 30 = 140

Answer:

1320

Step-by-step explanation:

59x5=295

295-25=270

270x5=1350

1350-30=1320

When solving for an unknown variable that has a number preceding it, you will divide both sides of the equation by this number, which is known as the ______________.

Answers

Answer: Coefficient

Step-by-step explanation:

When solving for an unknown variable that has a number preceding it, you will divide both sides of the equation by this number, which is known as the coefficient.

A coefficient is a number preceding any variable in a function for example, given the function 4x, the variable is 'x' and the number preceding it is 4. This number preceding the variable is what we call 'coefficient' of the variable 'x'

How does -1 to the 6th power equal -1? shouldn't it be positive?

Answers

(-1)^6=1\n-1^6=-1

The mean and standard deviation of a population being sampled are 64 and 6, respectively. If the sample size is 50, what is the standard error of the mean? how do I find the standard error?

Answers

SEM - Standard error of the mean;
You can find the standard error with a formula:
SEM = s / √n,   where s is the standard deviation and n is the sample size;
SEM = 6 / √50 = 6 / 7.071
Answer:
SEM = 0.8485 

Final answer:

The standard error is calculated as the standard deviation divided by the square root of the sample size. For a population with a standard deviation of 6 and a sample size of 50, the standard error is 6 / sqrt(50).

Explanation:

The standard error can be defined as the standard deviation divided by the square root of the number of samples. It helps to estimate the variability in the population. In this case, the mean is 64, the standard deviation is 6, and the sample size is 50. The equation to calculate the standard error is:  

Standard Error = Standard Deviation /  \sqrt(Sample Size).

Plugging in the values given in the question, we get:

Standard Error = 6 / \sqrt(50)

. After performing the division, you will get the standard error of the mean which tells you how far your sample mean could be from the true population mean.

Learn more about Standard Error here:

brainly.com/question/13179711

#SPJ12

Can someone simplify this please


(x^3+2x^2-4)+(3x^2+6)

Answers

Answer:

x³+5x²+2

Step-by-step explanation:

DM me if you have other questions!